Use of Random T-DNA Mutagenesis in Identification of Gene UvPRO1, A Regulator of Conidiation, Stress Response, and Virulence in Ustilaginoidea virens - Lv, Bo; Zheng, Lu; Liu, Hao; Tang, Jintian; Hsiang, Tom; Huang, Jinbin (Frontiers in Microbiology, 2016)
False smut of rice, caused by Ustilaginoidea virens (Cooke) Takahashi (teleomorph: Villosiclava virens), is one of the most important diseases affecting rice worldwide. Agrobacterium tumefaciens-mediated transformation was used to identify functional genes in U. virens. In this study, we selected a single-copy insertion mutant T133 with deficiency in producing conidia by screening the T-DNA insertion mutant library of U. virens. The UvPRO1-deletion mutant was successfully obtained after cloning the targeted gene by analysis of the T-DNA insert site of mutant T133. Further research showed that the UvPRO1 mutant was reduced in growth rate by 7.8% and could not produce conidia in PSB medium, while increased sensitivities to sodium dodecyl sulfate, Congo red and hyperosmotic stress increased. Moreover, the UvPRO1 deletion mutant hyphae could extend along the surface of spikelets at 1-3 dpi, but mycelia became wizened and completely lost the ability for infection of spikelets at 4 dpi. The relative expression level of UvPRO1 at 8 dpi was more than twice as high as that at 1-2 dpi. These results suggest that UvPRO1 plays a critical role in hyphal growth and conidiation, as well as in stress response and pathogenesis. The findings provided a novel mode of action for the PRO1 protein in fungi and improved the understanding of the function of UvPRO1 in the life cycle of U. virens.